Control of Individual Honey Locust Trees in Grazed Pasture - K. R. Harmoney (Kansas Agricultural Experiment Station Research Reports, 2016)
Honey locust (Gleditsia triacanthos) is a deciduous tree that produces large brown seed pods and thorny appendages, and is present throughout most of the US. The pods are highly nutritious for livestock and wildlife, and are easily spread by animals in dung pats. Honey locust is typically found in greatest concentrations in the central U.S. in the same general range as historical tallgrass prairie. Fire suppression and introduction of honey locust into shelter belts has allowed honey locust to increase into more arid regions associated with mixed grass prairie. When cut, honey locust is capable of producing abundant new sprouts from buds around the trunk and along the root system. Because of this, herbicides are usually required to effectively control trees when cut. Several herbicides have been labeled for honey locust control through various application techniques, including basal bark, thin line basal bark, cut stump, frill or girdle, and foliar applications. However, picloram, one of the most effective herbicides on honey locust, is not labeled for individual basal bark or cut stump treatment in grazed pasture. Aminopyralid recently received a new label addition for individual tree treatment of honey locust in grazed pasture.
Keywords: weed science